Enkulturasi Nilai-nilai Kristiani dalam Tradisi Batak melalui Lagu “Nunga Loja Daginghon” sebagai Bentuk Pendidikan Spiritual dalam Keluarga - Sarmauli, Sarmauli; Bate’e, Yamowa’a; Pransinartha, Pransinartha (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2022)
Singing nunga loja daginghon as a lullaby for children in the family has become an inseparable tradition in the life of the Christian Batak family. A spiritual song born in the socio-historical context of the poor and oppressed proletariat in Germany has been adopted into a lullaby spiritual song in Batak derived from Ende's book written with a description of the evening chant. The specialty of this song in the life of the Batak Christian family is interesting to examine with a qualitative approach through the study of literature in a musical and socio-historical perspective. This approach is done to find the background of this song used as a lullaby at night and also at the same time to find the meaning contained in this song as a medium of spiritual education for children in the life of the Christian Batak family. Researchers argue that based on an analysis of the song form and socio-historical context of Nunga Loja Daginghon's song, singing this song at night is very effective as a form of spiritual education for children in the context of Christian Batak family life. Menyanyikan lagu Nunga Loja Daginghon sebagai pengantar tidur bagi anak-anak dalam keluarga telah menjadi tradisi yang tidak dapat dipisahkan dalam kehidupan keluarga Batak Kristen. Lagu rohani yang lahir dalam konteks sosio-historis kaum proletar yang miskin dan tertindas di Jerman telah diadopsi menjadi lagu rohani pengantar tidur dalam bahasa Batak yang bersumber dari buku Ende yang ditulis dengan keterangan nyanyian pada malam hari. Keistimewaan lagu ini dalam kehidupan keluarga Batak Kristen menarik untuk ditelaah dengan pendekatan kualitatif melalui studi kepustakaan dalam perspektif musik dan sosio-historis. Pendekatan ini dilakukan untuk menemukan latar belakang lagu ini dijadikan sebagai lagu pengantar tidur pada malam hari dan juga sekaligus untuk menemukan makna yang terkandung dalam lagu ini sebagai media pendidikan spiritualitas bagi anak-anak dalam kehidupan keluarga Batak Kristen. Peneliti berpendapat bahwa berdasarkan analisis terhadap bentuk lagu dan konteks sosio-historis terhadap lagu Nunga Loja Daginghon, menyanyikan lagu ini pada malam hari sangat efektif sebagai bentuk pendidikan spiritualitas bagi anak-anak dalam konteks kehidupan keluarga Batak Kristen.